Impact of Intraseasonal Oscillations on the Activity of Tropical Cyclones in Summer Over the South China Sea: Nonlocal Tropical Cyclones - Ling, Zheng; Wang, Yuqing; Wang, Guihua; He, Hailun (Frontiers in Earth Science, 2020)
In addition to tropical cyclones (TCs) locally formed in the South China Sea (SCS), there were also TCs that initially form over the Northwest Pacific (NWP) and move westward to enter the SCS (often called nonlocal TCs). In this study, the impacts of two types of intraseasonal oscillations (ISOs), namely the Madden-Julian Oscillation (MJO) and the Quasi Biweekly Oscillation (QBWO), on nonlocally formed TCs over the SCS (nonlocal TCs) in summer (May-September) are analyzed based best-track TC data and global reanalysis during 1979–2018. Results show that in the convective phases of both MJO and QBWO, the western Pacific subtropical high shifted more eastward, and more TCs entered the SCS. This is mainly because more TCs formed in the NWP in the convective phases of ISOs and the genesis locations of the NWP TCs shifted westward and closer to the SCS. In addition to TC count, ISOs also affected the intensity of nonlocal TCs entered the SCS, with the influence of QBWO being more significant than MJO. In the convectively active phases of QBWO (phases 2 to 5), 34 nonlocal TCs reached typhoon intensity, while only 2 nonlocal TCs reached typhoon intensity in the convectively inactive phases (phases 1, 6, 7, 8). Further analysis indicates that nonlocal TCs often moved with the northwestward propagating convective signals of QBWO, resulting in more and stronger TCs that entered the SCS in the convective phases of QBWO. The mean location that the nonlocal TC entered the SCS also shifted northward with the northward propagation of ISOs.